Digital Teaching and Learning Scaffolding in Education: A Systematic Review Using Bibliometric Analysis - Luthpi Safahi; Herri Mulyono; Budhi Akbar; Abdul Hamid Busthami Nur; Ihsana El Khuluqo (International Journal of Engineering, Science and Information Technology, 2025)
This study aims to systematically analyze the evolution, research trends, and scientific impact of digital teaching and learning scaffolding through the application of bibliometric analysis. By employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 methodology, a total of 396 relevant journal articles published between 2013 and 2023 were identified from Google Scholar using Publish or Perish (PoP). The dataset was then analyzed using VOSviewer, with a specific focus on citation patterns, keyword co-occurrence, co-authorship networks, and thematic clusters. The bibliometric mapping revealed five dominant research clusters: (1) integration of digital technology in higher education, (2) learning strategies and their impact on students’ outcomes, (3) digital games and scaffolding approaches in children’s education, (4) teacher education development and practice, and (5) contextual influences in educational research. In addition, the study identifies prominent authors, highly influential publications, and major institutional as well as international collaborations, offering a comprehensive overview of the intellectual structure of the field. The findings highlight an increasing global interest in digital scaffolding in education, demonstrating its significant contributions to improving student engagement, cognitive development, problem-solving, and personalized learning experiences. Nevertheless, several challenges remain evident, particularly in terms of accessibility across diverse contexts, teacher readiness to adopt innovative pedagogies, and technological limitations within resource-constrained environments. This research contributes to the academic discourse by providing evidence-based insights and practical recommendations to optimize the implementation of digital scaffolding in contemporary educational settings. Moreover, it emphasizes the importance of continuous exploration of emerging technologies such as artificial intelligence (AI), virtual reality (VR), and adaptive learning systems to further strengthen the effectiveness and sustainability of digital scaffolding practices in the future.